WESTERN border area: MOVEMENT AND ETHNIC CHARACTERISTIC OF THE POPULATION (Annual of the Faculty of Philosophy in Skopje, 2008)
This study elaborates determined statistics concerning the movement and the ethnic and geographic characteristics of the population of the discussed municipalities from the western part of the Republic of Macedonia, whose territories partially or completely belong to the border area. The data has been presented and analyzed for each municipality, according to the information from the census in 1994 and old territorial map from 1996 and census in 2002 and new administrative territorial division from 2004. Although there is information about the population of the Republic of Macedonia, what lacks is a concrete analysis concerning the statistics about the movement and the ethnic structure of the population in the municipalities, according to the existing territorial division. The analyses of the population from different aspects including the strategic and geopolitics are very important.
Keywords: POPULATION; ETHNIC AND GEOGRAPHIC CHARACTERISTICS; MUNICIPALITY; CENSUS